Assessment of Information Technology Use Competence for Teachers: Identifying and Applying the Information Technology Competence Framework in Online Teaching - Phan Chi, Thanh; Ngo Tu, Thanh; Phan Minh, Tien (Journal of Technical Education and Training, 2020)
This paper proposes a theoretical framework as a foundation for building information technology competence framework and the requirements for using information technology competence of teachers in online teaching at training institutions. The parameters in this paper survey was conducted on sample space (n = 342) and 42 expert opinions to identify information technology competence framework with criteria and skill sets necessaries to successfully organize online teaching. This paper discusses on teaching developing information technology competence to change minds and develop teachers' competency to meet the online teaching trend of the digitalization today. So, building information technology competence framework in online teaching has many meanings in training process contribute to improving the learning capacity of students.